2012
DOI: 10.1021/om300202p
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Zirconocene–Carboryne with Alkenes: Synthesis and Structure of Zirconacyclopentanes with a Carborane Auxiliary

Abstract: Reaction of zirconocene−carboryne in situ generated from Cp 2 Zr(μ-Cl)(μ-C 2 B 10 H 10 )Li(OEt 2 ) 2 with various alkenes RCHCH 2 in refluxing toluene gave the monoinsertion products 1in good to high isolated yields with very high regioselectivity, depending on the polarity of the alkenes. This reaction offered an efficient route to zirconacyclopentanes with a carborane auxiliary, which can be viewed as a carborane version of zirconacyclopentanes. They are thermally very stable and chemically inert toward uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 60 publications
1
9
0
1
Order By: Relevance
“…Moreover, 2,4-diphenyl-(6, ~15%), 2,5-diphenylalumolane (7, ~3%), and 2-phenylaluminacyclopropane (8, ~7%) were identified as minor products. A similar regioselectivity dependence on the alkene structure was observed in the formation of zirconacyclopentane structures [7].…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…Moreover, 2,4-diphenyl-(6, ~15%), 2,5-diphenylalumolane (7, ~3%), and 2-phenylaluminacyclopropane (8, ~7%) were identified as minor products. A similar regioselectivity dependence on the alkene structure was observed in the formation of zirconacyclopentane structures [7].…”
Section: Introductionsupporting
confidence: 66%
“…According to Scheme 9, complex 17 can be formed as a result of dissociation of the intermediates LM3 and LM4. The estimation of the thermodynamic probability of the LM1-LM4 dissociation to 16, 17 with elimination of the ethylene molecule by reactions (6) and (7) (Scheme 9) showed that only low-energy complexes with styrene LM3 and LM4 can be converted to the zirconacyclopropane 17 (Table 1) suggests the equilibrium on the stages (6) and (7). The same transformations for LM1 and LM2 are energetically unfavorable (ΔG r 298 ≥ 0).…”
Section: Mechanism Of By-products Formation In the Catalytic Styrene mentioning
confidence: 99%
“…32 The results show that electron-withdrawing aryl substituents go to the a position, whereas the electron-donating alkyl substituents prefer the b position. The resultant zirconacycles incorporating a carboranyl unit are also thermally stable and chemically inert toward unsaturated organic molecules.…”
Section: Reaction With Alkenesmentioning
confidence: 95%
“…Nickel-mediated three-component cycloaddition reaction of carboryne, alkenes and alkynes 过渡金属-碳硼炔配合物的反应性质取决于金属中 心的性质, 其中镍-碳硼炔 1 与炔烃作用可以获得与两 分子相同炔烃的[2+2+2]环加成产物 [21] , 而锆-碳硼炔 前体 3 只能与一分子炔烃发生 Zr-C 键插入反应, 得到 稳定的碳硼烷并锆杂环戊烯产物 4 [22] . 此锆杂五元环化 合物并不能进一步与炔烃反应, 考虑到镍杂五元环化合 物更高的反应活性, 4 在 NiCl 2 (PMe 3 ) 2 存在下可以与另一 分子炔烃反应(Scheme 2) [23] : 2009 年, 谢作伟课题组 [24] [25] , 插入反应的区域选择性由烯烃上 取代基的电性决定(Scheme 5): 给电子烷基位于金属 β 位(8a)而吸电子芳基位于金属 α 位(8b). 同样 8 与炔烃在 NiCl 2 存在下进一步反应, 能以最高 88%收率合成二氢 苯并碳硼烷 9 [26] 二氢富烯并碳硼烷化合物 11 (Scheme 7) [27] .…”
Section: 碳碳-取代碳硼烷衍生物的合成unclassified